2013
DOI: 10.1021/jo4014996
|View full text |Cite
|
Sign up to set email alerts
|

Cyclohexanones by Rh-Mediated Intramolecular C–H Insertion

Abstract: Some long chain α-aryl α-diazo ketones under Rh catalysis cyclize efficiently to the corresponding cyclohexanones. This is in marked contrast to the cyclizations of α-diazo β-ketoesters, which consistently deliver cyclopentanone products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…13 Monteiro synthesised 2-phenylsulfonyl cyclopentanones from α-diazo-β-keto sulfones via C-H insertion in good yields of up to 75%, which was comparable to their ester equivalents. 12 For the first twenty years of research in this area the vast majority of carbocyclic rings formed were five membered, with some exceptions, [17][18][19] when the insertion occurs into the sulfonyl group rather than the carbonyl containing chain the presence of the sulfone alters the geometry of the C-H insertion transition state enabling access to six membered thiopyrans, and, where the six membered ring is not accessible, five membered sulfolanes (Scheme 1). 17,[20][21][22] Scheme 1 Copper catalysed C-H insertion reactions of α-diazo-β-oxo-sulfones.…”
mentioning
confidence: 99%
“…13 Monteiro synthesised 2-phenylsulfonyl cyclopentanones from α-diazo-β-keto sulfones via C-H insertion in good yields of up to 75%, which was comparable to their ester equivalents. 12 For the first twenty years of research in this area the vast majority of carbocyclic rings formed were five membered, with some exceptions, [17][18][19] when the insertion occurs into the sulfonyl group rather than the carbonyl containing chain the presence of the sulfone alters the geometry of the C-H insertion transition state enabling access to six membered thiopyrans, and, where the six membered ring is not accessible, five membered sulfolanes (Scheme 1). 17,[20][21][22] Scheme 1 Copper catalysed C-H insertion reactions of α-diazo-β-oxo-sulfones.…”
mentioning
confidence: 99%
“…373 Since Taber and co-workers have also shown that, in favorable cases, α-aryldiazoketones will cyclize to form cyclohexanones in preference to cyclopentanones, due to the more electronically discriminating nature of the derived metal carbenes, when compared with carbenes derived from α-diazoesters (Scheme 145). 377 The formation of six-membered rings by C−H insertion has also been reported in specific cases, and in cases where five-membered ring formation is not possible. 378 Both studies employed chiral rhodium(II) carboxylate catalysts formed from N-protected amino acids, with 12% ee recorded by McKervey for insertion of an α-diazo-β-ketosulfone substrate and 24% ee obtained by Hashimoto and Ikegami for C−H insertion with a related α-diazo-β-ketoester.…”
Section: Catalytic Asymmetric C−h Insertion Reactionsmentioning
confidence: 98%
“…All epoxides were stirred for a few days over CaH 2 , vacuum distilled, and degassed by freeze-pump-thaw prior to use. NaCo(CO) 4 [45], 5,6-epoxyhexanenitrile, 3,4-epoxybutyl butyrate [46], cyclohexyl oxirane [47], 2-(tert-butyl)oxirane [48], and 2-benzyl oxirane [49] were synthesized following previously reported methods.…”
Section: General Considerationsmentioning
confidence: 99%